2010
DOI: 10.1371/journal.pone.0011449
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modifications of the Brain in Acclimatization to High-Altitude

Abstract: Adaptive changes in respiratory and cardiovascular responses at high altitude (HA) have been well clarified. However, the central mechanisms underlying HA acclimatization remain unclear. Using voxel-based morphometry (VBM) and diffusion tensor imaging (DTI) with fractional anisotropy (FA) calculation, we investigated 28 Han immigrant residents (17–22 yr) born and raised at HA of 2616–4200 m in Qinghai-Tibetan Plateau for at least 17 years and who currently attended college at sea-level (SL). Their family migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 70 publications
5
85
1
Order By: Relevance
“…In females from high altitude, a significant decrease in both systolic and diastolic pressure when compared to females from Arica is also observed. Similar results were observed by Zhang et al, (2010) working with a high altitude Tibetan population, where males showed a significant decrease in heart rate.…”
Section: Discussionsupporting
confidence: 84%
“…In females from high altitude, a significant decrease in both systolic and diastolic pressure when compared to females from Arica is also observed. Similar results were observed by Zhang et al, (2010) working with a high altitude Tibetan population, where males showed a significant decrease in heart rate.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, these data identify similar locations of altered white matter water mobility as those observed previously in individuals after prolonged sojourns to high altitude 8,17,18 and in individuals native to high altitude. 19 It should be mentioned that by directly calculating T 2 and mean diffusivity, we avoided any potential confusion that 'T 2 -shine through' can cause on raw diffusion-weighted images. Our findings of no overt increases in T 2 during hypoxia preclude the possibility of T 2 shine through on the raw diffusion-weighted image, which normally occurs when there is an increase in T 2 in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…2010, 2011a), developmental experience of childhood, and adolescence (Zhang et al. 2010), or intermittent sea‐level (SL) normoxic exposure (Wang et al. 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, increases in FA values in the corticospinal tract and CC were only found in HA immigrant descendants (Zhang et al. 2010). This hypoxia‐adaptive genetic trait of callosal fiber modification indicates that CC may play a crucial role in brain anatomical architecture during HA acclimatization.…”
Section: Introductionmentioning
confidence: 99%